Distributed and centralized autonomous DC microgrid for residential buildings: A case study. (January 2020) - Chauhan, Rajeev Kumar; Chauhan, Kalpana; Subrahmanyam, B. Ravi; Singh, Avanish Gautam; Garg, Man Mohan
Abstract: This paper proposes a control algorithm for distributed and centralized autonomous DC microgrid system. The DC microgrid consists of five houses of roof top mounted photovoltaic (PV) plant, battery banks and their loads. In case of distributed system, each house PV plant and battery bank are responsible to supply their own load (i.e. not interconnection between houses). While in case of centralized system, a centralized battery bank (CBB) is connected to the DC microgrid and all the five houses are connected in parallel with the CBB. The CBB is responsible to supply the surplus load of all the five houses as well as to consume their surplus PV power. This type of connection provides an opportunity to interconnect the houses with each other. The comparative study shows that the peak power demand of the microgrid decreased significantly. Therefore the small size of the battery bank and PV plant is needed to supply the same amount of power demand of five houses. The aim of the paper is to find out the solution for minimization of the size of the PV panel and battery bank. The finding shows that in the centralized system 0.31% less PV energy required to be generated, also 1.55% battery energy and 1.45% of energy losses can be saved, hence resulting in a 4.71% reduction in capital cost as compared to that of distributed system. Highlights: The peak power demand of the microgrid decreased significantly. Resuction in the size of PV plants for same power delivery. Reduction in size of battery bank for feeding same load.